Functional Foods - Lagouri, Vasiliki (IntechOpen, 2019)
"Let food be thy medicine and medicine be thy food" said Hippocrates, the father of medicine approximately 2500 years ago. Is food also medicine? Are products that intend to cure diseases medicinal products and not food? Do we know the combination of foods or food components with functional properties that can help promote the well-being or reduce the risk of chronic diseases? In general terms, all foods are functional because they provide the nutrients necessary for a healthy diet. So what are the components that functional foods have beyond their nutrition value? What is the definition of functional foods? What scientific research is needed to validate health claims for functional foods? This book will provide answers to all of these questions. It is important for scientists to have the opportunities to study the relationship between a food type or a food active component and the improved state of health or reduction of diseases. The communication of health benefits to consumers is of critical importance so that they have the knowledge to make informed choices about the foods they eat and enjoy.